2019
DOI: 10.3390/w11030502
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hybrid Data-Intelligence Model for Forecasting Monthly Rainfall with Uncertainty Analysis

Abstract: In this research, three different evolutionary algorithms (EAs), namely, particle swarm optimization (PSO), genetic algorithm (GA) and differential evolution (DE), are integrated with the adaptive neuro-fuzzy inference system (ANFIS) model. The developed hybrid models are proposed to forecast rainfall time series. The capability of the proposed evolutionary hybrid ANFIS was compared with the conventional ANFIS in forecasting monthly rainfall for the Pahang watershed, Malaysia. To select the optimal model, sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Owing to the fact that standalone AI models experienced some limitations on tuning their internal parameters for an optimal learning process [32], the current study is adopted based on the integration of a nature-inspired optimization algorithm called Genetic Algorithm (GA) with a Random Forest (RF) model. The GA optimization approach was demonstrated as a reliable technique in tuning AI models for multiple engineering applications and thus it was selected for the current study [33][34][35].…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the fact that standalone AI models experienced some limitations on tuning their internal parameters for an optimal learning process [32], the current study is adopted based on the integration of a nature-inspired optimization algorithm called Genetic Algorithm (GA) with a Random Forest (RF) model. The GA optimization approach was demonstrated as a reliable technique in tuning AI models for multiple engineering applications and thus it was selected for the current study [33][34][35].…”
Section: Research Backgroundmentioning
confidence: 99%
“…The algorithm gained significant important because it is invariant under scaling and it is robust to the inclusion of irrelevant features [38]. Several studies examined the application of Random Forest in engineering applications and demonstrated its feasibility in prediction processes [26,34,35]. Under the bootstrapping method, the data during the training phase are selected randomly and independently to develop an RF model, and the data that are not involved in the selection process are named "out-of-bag" [39].…”
Section: Random Forest Modelmentioning
confidence: 99%
“…Determination of optimum inputs is an important task in any system identification or hydrological modeling problem that dictates the accuracy/complexity of evolved models. In previous studies, different input combinations were examined via trial and error method to determine suitable predictors (e.g., [28,42]). However, this is time-consuming, and the modeler might not achieve the best inputs if it is not considered as the potential predictor in advance.…”
Section: Determination Of Optimum Predictorsmentioning
confidence: 99%
“…In a recent study, Danandeh Mehr et al [9] confirmed that the firefly optimization algorithm can be used to determination of SVM parameters and increase its predictive accuracy. More recently, Yaseen et al [42] hybridized an adaptive neuro-fuzzy inference system model with the evolutionary algorithms including particle swarm, genetic algorithm, and differential evolution. The capability of the proposed hybrid models for precipitation forecasting was compared with the conventional neurofuzzy model.…”
Section: Introductionmentioning
confidence: 99%
“…This may be the result of stations being relocated because of urbanization, errors in the methods implemented for measuring the rainfall amount, or the breakdown of instruments for a specific period, particularly in areas of flooding [2]. The analysis results of metrological and hydrological models can be affected in cases that include rainfall data series with missing values [3]. As a result, filling the gaps left by the missing data and estimating the missing values has become very important in recent hydrological studies [2].…”
Section: Introductionmentioning
confidence: 99%